Web writing : why and how for liberal arts teaching and learning - Dougherty, Jack; O'Donnell, Tennyson Lawrence, 1973- (Digital humanities (Ann Arbor, Mich.), 2015)
The essays in Web Writing respond to contemporary debates over the proper role of the Internet in higher education, steering a middle course between polarized attitudes that often dominate the conversation. The authors argue for the wise integration of web tools into what the liberal arts does best: writing across the curriculum.--Provided by publisher.